Uji Sensori dan Uji Kadar Kimia Flakes Berbahan Dasar Tepung Porang (Amorphophallus muelleri) dan Tepung Kacang Hijau (Vigna Radiate) - Herly Nainggolan; Novriani Tarigan; Elsa Grace Laura Sipahutar; Fransiskanes Marselia Tampubolon; Siti Hadijah Siregar (Universitas Muhammadiyah Manado, 2025)
Background: Porang contain glucomannan. Glucomannan is a water-soluble fiber, and has low calories, so porang needs to utilize its nutritional value in food products. The addition of mung beans to flakes products will add nutritional value because they contain iron, vitamin C and zinc. Objective: The aim of the research was to determine the sensory value and chemical content (carbohydrate, protein, fat, water, ash, crude fiber and breakability) of porang flour flakes and mung bean flour. The research use experimental method with a completely randomized design (CRD) with 3 formulations, namely F1 (60%:40%), F2 (50%:50%), F3 (40%:60%). The parameters observed were sensory tests involving 50 panelists. Chemical content test methods include: carbohydrate by difference method, protein by Kjeldhal method, fat by Soxhlet method, content (water, ash and crude fiber) using the gravimetric method, breakability by tensile strength method. Sensory test data were analyzed using ANOVA and Chemical test data was quantitatively descriptively. Result: The F1 sensory test results showed a color value of 3.51, aroma 3.37, texture 3.33, taste 3.14. F2 shows a color value of 3.14, aroma 3.47, texture 3.46, taste 3.27. F3 shows a color value of 3.72, aroma 3.98, texture 3.76, taste 3.83. The average value of chemical test content (carbohydrates, protein, fat, water, ash, crude fiber and breakability) respectively is 74.85%, 9.35%, 4.76%, 6.64%, 4.39 %, 2.29%, and 12.16 N. Conclusion: Porang flour and mung bean flour have an influence on sensory tests (color, aroma, texture, taste) and chemical content tests (carbohydrate, protein, fat, water, ash, crude fiber, breakability).